METHODS OF DEVELOPING INDEPENDENT LEARNING IN THE MODULAR-CREDIT SYSTEM - Tursunov Shavkat Khusenovich (Web of Journals Publishing, 2025)
This article explores the theoretical and practical aspects of organizing independent learning for students within the modular-credit system. The study analyzes the essence of the modular-credit system, its advantages, methods for effectively organizing independent learning, and assessment mechanisms. Based on local and international experiences, the article examines ways to improve students' self-development activities. The research findings offer recommendations for enhancing independent learning and improving the quality of education within the modular-credit system.
Keywords: Modular-credit system, independent learning, assessment mechanism, educational process, innovative pedagogical technologies, student participation, self-analysis, distance learning, learning module, credit volume.